2022
DOI: 10.1021/acscentsci.2c00981
|View full text |Cite
|
Sign up to set email alerts
|

Breathing and Tilting: Mesoscale Simulations Illuminate Influenza Glycoprotein Vulnerabilities

Abstract: Influenza virus has resurfaced recently from inactivity during the early stages of the COVID-19 pandemic, raising serious concerns about the nature and magnitude of future epidemics. The main antigenic targets of influenza virus are two surface glycoproteins, hemagglutinin (HA) and neuraminidase (NA). Whereas the structural and dynamical properties of both glycoproteins have been studied previously, the understanding of their plasticity in the whole-virion context is fragmented. Here, we investigate the dynami… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
46
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 143 publications
2
46
0
Order By: Relevance
“…Finally, all-atom studies reported good accord with hydrogen–deuterium mass spectroscopy, SAXS, and magic angle spinning solid-state NMR ,, data. In addition, the recent demonstration of antigenic sites on the influenza A surface glycoproteins is in accord with structural studies for that system, illustrating the predictive power of these simulations. Moreover, for coarse-grained models, validation has been performed by comparing the outcomes to all-atom simulations. , Overall, such comparisons generate confidence in simulation results for each model’s spatial and temporal regimes.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Finally, all-atom studies reported good accord with hydrogen–deuterium mass spectroscopy, SAXS, and magic angle spinning solid-state NMR ,, data. In addition, the recent demonstration of antigenic sites on the influenza A surface glycoproteins is in accord with structural studies for that system, illustrating the predictive power of these simulations. Moreover, for coarse-grained models, validation has been performed by comparing the outcomes to all-atom simulations. , Overall, such comparisons generate confidence in simulation results for each model’s spatial and temporal regimes.…”
Section: Discussionsupporting
confidence: 54%
“…Among the largest systems studied to date with all-atom MD is the viral envelope of influenza A by Amaro and co-workers, , which included the glycoproteins hemagglutinin (HA) and neuraminidase (NA), the proton channel M2, and a phospholipid bilayer. NA cleaves sialic acid residues from host-cell receptors, thereby assisting in viral particle release.…”
Section: All-atom Molecular Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…207 The Amaro group recently reported impressive mesoscale, all-atom MD simulations of two evolutionary-linked glycosylated influenza A virions. 208 The simulations reveal the main molecular motions of the principal surface antigenic targets of the influenza virus, hemagglutinin (HA), and neuraminidase (NA). Indeed, NA head tilting, HA ectodomain tilting, and HA head breathing are characterized at full atomistic resolution.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in molecular dynamics (MD) simulation methodologies (in particular, where they leverage machine learning algorithms for enhanced/efficient sampling) as well as access to ever increasing amounts of computational resources have meant that molecular simulation of entire viral particles has become tractable. In a recent issue of ACS Central Science , Amaro and co-workers characterize the dynamics of the two surface glycoproteins of influenza A using atomistic simulations of virion envelope models …”
mentioning
confidence: 99%